1988
DOI: 10.1002/ar.1092220308
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in the ventral region of the neural retina during the early development of the chick embryo eye

Abstract: The present study deals with morphologic and quantitative changes that take place in the area of cell death in the ventral part of the presumptive retinal wall of the chick embryo. These changes were followed from the optic vesicle stage until the first optic fiber fascicles leave the neural retina. Our results show that both the volume occupied by the area of cell death and the density of its pyknotic fragments undergo considerable variation during the period between Hamburger and Hamilton's (1951) stages 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 38 publications
2
54
0
1
Order By: Relevance
“…This decrease was more evident in the proximal pole of the cup (compare Fig. 6H,I with 6E,F) corresponding to the region where the optic fissure normally forms (Martín-Partido et al, 1988;Ozeki et al, 2000;Silver and Hughes, 1973). Altogether, these data indicate that Bmp7-mediated signalling controls proliferation and programmed cell death of RF precursors.…”
Section: Bmp7 Regulates Proliferation and Apoptosis During Optic Fissmentioning
confidence: 62%
“…This decrease was more evident in the proximal pole of the cup (compare Fig. 6H,I with 6E,F) corresponding to the region where the optic fissure normally forms (Martín-Partido et al, 1988;Ozeki et al, 2000;Silver and Hughes, 1973). Altogether, these data indicate that Bmp7-mediated signalling controls proliferation and programmed cell death of RF precursors.…”
Section: Bmp7 Regulates Proliferation and Apoptosis During Optic Fissmentioning
confidence: 62%
“…In various fishes, it is not always easy to isolate the peaks of morphogenetic and early neural cell death, probably due to the accelerated initial development when compared to higher vertebrates (Candal et al, 2005;Iijima and Yokohama, 2007). In chick (Martín-Partido et al, 1988), the numbers reported are very similar for the morphogenetic and early neural phases (1515 vs. 1680 pyknotic fragments, respectively). In the mouse, it is again impossible to isolate these peaks of cell death (Péquignot et al, 2003).…”
Section: Early Neural Cell Death Affecting Retinal Ganglion Cell Genementioning
confidence: 73%
“…Apoptosis has also been analyzed during the development of the chick retina (Cuadros and Ríos, 1988;Martín-Partido et al, 1988;Frade et al, 1996;Díaz et al, 1999Díaz et al, , 2000Mayordomo et al, 2003). Two waves of programmed cellular death occur in the developing chicken retina.…”
Section: Birdsmentioning
confidence: 99%